Fuzzy logic energy management for a microgrid with storage battery. Issue 10 (23rd August 2020) - Aristizábal, Andrés Julián; Hernán Ospina, Daniel; Castañeda, Mónica; Zapata, Sebastián; Banguero, Edison
ABSTRACT: This article presents the development of an energy management system using fuzzy logic applied to a microgrid that combines photovoltaic solar energy, wind energy and a storage system with batteries. The model was developed using LabVIEW software and allows to obtain performance results of the photovoltaic generator, the wind turbine and the battery bank. The energy management system can be controlled in real time to take advantage of existing weather conditions. The results indicate that the fuzzy logic system guarantees the continuous operation of the load through the energy resources of the microgrid. The designed microgrid allows to generate 63, 288 kWh/year of photovoltaic solar energy and 40, 175 kWh/year of wind energy.